Konservasi Tanaman Pangan, Obat, dan Pewarna Berdasarkan Kearifan Lokal Masyarakat Desa Sesait, Kecamatan Kayangan, Kabupaten Lombok Utara - Jupri, Ahmad; Isrowati, Isrowati; Maulida, Baiq Rizki; Aini, Diah Kurotul; Rabani, M. Restu; Ichsani, Qatrunnadia; Ramadhani, Baiq Isna Rizka; Wirahadi, Muhammad Rosyid; Wulandari, Suci Yulia; Hidayati, Lilik (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
The history of Sesait Village, which used to be 90% of the Kayangan sub-district area. The tradition in Sesait Village is the rules for nurak like "aji makem" in the belek grave. This tradition uses plants as the main ingredients in this tradition. The plants used are betel leaves, bitter melon (pare bulu/pare rau), beleleng, elas. The food, dye and medicinal plants in Sesait Village are very diverse. Food, dye and medicinal plants have various benefits, not only as food, dye and medicinal plants. Efforts to conserve food, dye and medicinal plants are carried out by the people of Sesait Village by planting these plants in their own yards